Marketing your consulting or professional services - Karlson, David (Crisp Pub. Menlo ParkUS, 1988)
Presents the methodology for professionals to develop and implement a more aggressive marketing programme. Covers important marketing basics including: how to develop a marketing strategy based on research; how to assess competition; and how to keep clients satisfied.